2022
DOI: 10.34172/jlms.2022.49
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Anti-tumor Effects of Photodynamic Therapy on Oral Squamous Cell Carcinoma: A Review

Abstract: Introduction: Due to the increasing prevalence and high mortality rate of oral squamous cell carcinoma (OSCC) and problems with its routine treatments, more recent modalities like photodynamic therapy (PDT) have been developed. PDT effectively destroys tumor cells with minimum side effects. Research on in vitro effects of PDT may be helpful in determining the molecular mechanisms responsible for its effectiveness and can lead to the development of more efficient techniques. The aim of this study was to review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…They confirmed that PaH-PDT increases the percentage of cells in the G0/G1 phase and decreases the CDK2 and cyclin E1 protein levels ( 135 ). However, it is shown that 5-aminolaevulinic acid (5-ALA) as a second generation of protoporphyrin IX PSs in PDT has no effect on CC but, as radiosensitizer (for gamma radiation), can stop oral squamous cell carcinoma at G2/M stage ( 136 , 137 ). Furthermore, it is reported by Sengupta and collogues that Fe 3 O 4 nanoparticles (NPs) on porphyrins has immune-protective effects and capable apoptosis via upregulations of p21 kinase by CCA at the G0/G1 stage in AGS and RAW cell lines ( 140 , 142 ).…”
Section: Cca Following Pdtmentioning
confidence: 99%
“…They confirmed that PaH-PDT increases the percentage of cells in the G0/G1 phase and decreases the CDK2 and cyclin E1 protein levels ( 135 ). However, it is shown that 5-aminolaevulinic acid (5-ALA) as a second generation of protoporphyrin IX PSs in PDT has no effect on CC but, as radiosensitizer (for gamma radiation), can stop oral squamous cell carcinoma at G2/M stage ( 136 , 137 ). Furthermore, it is reported by Sengupta and collogues that Fe 3 O 4 nanoparticles (NPs) on porphyrins has immune-protective effects and capable apoptosis via upregulations of p21 kinase by CCA at the G0/G1 stage in AGS and RAW cell lines ( 140 , 142 ).…”
Section: Cca Following Pdtmentioning
confidence: 99%
“…Compared with the predominantly utilized photosensitizer, 5-aminolevulinic acid (5-ALA), which exhibits excitation and emission within the visible light spectrum, ICG demonstrates excitation and emission within the near-infrared wavelength range [ 6 ]. This characteristic facilitates a significantly enhanced penetration depth in human tissues, consequently potentially leading to a more profound tumor eradication capacity [ 7 , 8 ]. Previous research conducted in our laboratory has revealed that ICG can induce ferroptosis in cancer cells when exposed to infrared light, and its photothermal effect after NIR irradiation has also been reported [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite its low popularity, this is a well-tested, clinically approved, and effective method of cancer treatment [ 4 , 5 , 6 ]. Accurate knowledge of PDT mechanisms gives a chance for better understanding of this treatment [ 7 ]. Additionally, PDT causes cellular acting, including an impact on the endocrine and immunological pathways.…”
Section: Introductionmentioning
confidence: 99%